Language and emotion: Teachers’ ethical-political suffering regarding “gender-neutral language” approach in schools - Ribas, Dianna de Oliveira (The ESPecialist, 2025)
Frequent initiatives to limit teachers’ autonomy, as well as to monitor their pedagogical practices, create specific situations of social suffering that are scarcely explored in academic circles. Influenced by socio-historical-cultural theory and the socio-historical approach to psychology, this article aims to explore the ethical-political dimension of teachers’ suffering related to addressing gender issues in schools, particularly concerning the use of "neutral" language in educational institutions and the inclusion of LGBTQIA+ students. Data collection was conducted in a municipal public educational institution located in the coastal region of Rio de Janeiro, through interviews with 8 Language teachers working in lower secondary education. The theoretical foundation guiding this research is based on the works of Spinoza (2007), Vygotsky (2009), and Sawaia (1999), emphasizing the recognition of affectivity as constitutive of the subject, the influence of the philosophy of affects, and the exclusion/inclusion dialectic. The adopted methodology is qualitative in nature, focusing on the choice of ethical-political suffering as an analytical tool, in line with Souza Santos’ (1997) suggestion that the humanities should include destabilizing categories in the analysis of social issues.